GROWTH AND NUTRITIONAL ANALYSIS OF TREE SPECIES IN CONTAMINATED SUBSTRATE BY LEACHABLE HERBICIDES - Fiore,Rebecca de Araújo (2016)
ABSTRACT Ecosystems contamination by residues of pesticides requires special attention to the herbicides subject to leaching. The objective was to select tree species to rhizodegradation contaminated by residues of 2,4-D and atrazine and to recompose riparian areas to agricultural fields, then reducing the risk of contamination of water courses. A total of 36 treatments consisted of the combinations of forest species were evaluated [Inga marginata (Inga), Schizolobium parahyba (guapuruvu), Handroanthus serratifolius (ipê amarelo), Jacaranda puberula (carobinha), Cedrela fissilis (cedro), Calophyllum brasiliensis (landin), Psidium mirsinoides (goiabinha), Tibouchina glandulosa (quaresmeira), Caesalpinia férrea (pau-ferro), Caesalpinia pluviosa (sibipiruna), Terminalia argêntea (capitão) and Schinopsis brasiliensis (braúna)] and three solutions simulating leachate compound (atrazine, 2,4-D and water - control), with four replicates each. The characteristics measured were plant height, stem diameter, number of leaves, leaf area and dry biomass, and foliar nutrition. Forest species survived the herbicide application, and most showed an increase in macronutrients even under an herbicide application, and the Inga had the highest tolerance regarding growth analysis. It is recommended to use species that are more tolerant to Atrazine and 2,4-D in field experiments to confirm previous results of this simulation.